Methods and validity indicators for measuring adherence and persistence to aspirin in secondary cardiovascular prevention: a systematic review - Nouni-García, Rauf; Ramirez-Familia, Elisabeth; López-Pineda, Adriana; Esquerdo-Arroyo, Amanda; Carbonell-Soliva, Álvaro; Martínez-Muñóz, María; Compañ Rosique, Antonio F.; Quesada, Jose A.; Carratalá-Munuera, Concepción; Gil-Guillén, Vicente F. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAspirin (acetylsalicylic acid, ASA) is widely recommended for long-term secondary cardiovascular prevention (SCP), but its clinical effectiveness depends on patient adherence, which remains suboptimal. Understanding how adherence and persistence to ASA are measured is essential to improving outcomes. This systematic review aimed to identify the methods used to assess adherence and persistence to ASA in SCP and evaluate their validity indicators.MethodsWe systematically searched EMBASE, MEDLINE, and Scopus for studies published up to October 30, 2023, reporting methods for measuring adherence or persistence to ASA in adults undergoing secondary cardiovascular prevention. Two reviewers independently screened articles and extracted data on study characteristics, measurement methods, and validity indicators. The results were synthesized in tabular form according to method type (indirect or direct) and outcome assessed (adherence or persistence). Risk of bias was evaluated for studies that conducted validation analyses of the measurement methods.ResultsForty studies were included, most conducted in the United States. Indirect methods predominated: self-report questionnaires (45%, n = 18) and pharmacy dispensing records (32.5%, n = 13) were the most common tools for assessing adherence. Direct methods, such as platelet function tests or biochemical assays, were less frequently used (25%, n = 10). For persistence, dispensing records were the most used method (70%, n = 7). No indirect method reported validation specifically for ASA adherence or persistence. Validity indicators were only partially available for some direct methods.ConclusionsAdherence and persistence to ASA in SCP are primarily measured through indirect methods, with a lack of specific validation for ASA. There is a critical need to develop standardized, validated tools that integrate both direct and indirect measures and address gender-specific barriers to adherence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023470993, PROSPERO identifier CRD42023470993.